AB0794 Intra-Articular Injections in Thumb Osteoarthritis. A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (10th June 2014) - Trellu, S.; Dadoun, S.; Fautrel, B.; Gossec, L.
Abstract : Background: Intra-articular injections of corticosteroids (CS) or hyaluronic acid (HA) are reported to be efficacious in hip and knee osteoarthritis (OA). In base of thumb OA (rhizarthrosis), information concerning intra-articular injections efficacy is conflicting. Objectives: To assess efficacy on pain, function and muscular force of intra-articular injections of CS or HA in thumb OA. Methods: A systematic review of the literature in PUBMED, EMBASE, Cochrane library and congress abstracts was performed until August 2013. All randomised controlled trials (RCTs) reporting the efficacy of HA or corticosteroids or both in thumb OA were selected. Data were collected using a predetermined form. The outcomes were visual analog scale for pain, functional capacity score as available (in percentage of the maximum possible score) and pulp pinch force at 4, 12 and 24 weeks after injection as available. In each trial, the standardized response mean (SRM) was calculated to assess the magnitude of treatment effect. Pooled SRMs were assessed by meta-analysis using the Mantel-Haenszel method. All meta-analyses were carried out with use of random-effects model in case of significant heterogeneity. Results: 6 RCTs contributed to 3 meta-analyses (HA versus placebo, CS vs placebo and HA vs CS). Among the 390 patients, 169 were treated with HA, 147 with CS and 74 with placebo: mean age 63±2.3 years; 86% were female. The number of injections varied from 1 to 3. In the meta-analysis comparing HA to placebo (2 RCTs, 148 patients), a difference was evidenced on functional capacity at week 12 (SRM -1.14 [-1.69; -0.60]) with no difference on pain. In the meta-analysis comparing CS to placebo (2 RCTs, 164 patients), no difference was evidenced. In the meta-analysis comparing HA to CS (4 RCTs, 304 patients), there was no difference on pain, function and pulp pinch force until week 12. At week 24, pain VAS was significantly lower in CS group (SRM -1.44 [-2.74; -0.14]) and pulp pinch force better in the HA group (SRM -0.75 [-3.87; 1.97]) and there was no difference in function. Conclusions: This work suggests similar short-term benefits with HA or CS injections in thumb OA whereas at longer-term follow-up, CS may lead to more pain relief and HA lead to higher pulp pinch force. New studies should be performed to confirm these results. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2692